Komunikasi Synchronous dan Asynchronous dalam e-Learning pada Masa Pandemic Covid-19 - Muhammad Hanif Fahmi (Jurnal Nomosleca, 2020)
The impact of the Corona Virus Disease 2019 (Covid-19) pandemic requires educational institutions to implement Learning from Home (BDR) activities through the online distance learning method (PJJ daring) using e-learning. Educational institutions that have been using direct communication in learning have switched to learning using online media (mediated communication). Some communication media in e-learning can only run in synchronous or asynchronous mode, some others can run in both modes. This study aims to determine the preferences of educators and students in choosing the type and communication media used in e-learning in the implementation of BDR. Qualitative methods with a comparative descriptive approach are used to describe and compare the functions, advantages and disadvantages of each communication media as well as to see the preferences for the use of communication media in online distance learning. The learning process that occurs today, mostly uses a hybrid communication mode that combines synchronous and asynchronous communication. In choosing communication media that are used for PJJ daring (e-learning), educators consider several factors, including: data quota consumption, user friendly, network infrastructure conditions, and conformity to learning activities. So that educators and students have high preferences for several applications such as Whatsapp, Zoom Meeting, Google Meet, Microsoft team, Google Clasroom, Google forms, Quizziz to be used together.Keywords: Synchronous Communication, Asynchronous Communication, Learning From Home, Online PJJ, e-Learning